The Lived Experience of Nursing Students Consolidating in the Intensive Care Unit - Renick, Paul (Université d'Ottawa / University of Ottawa, 2026)
Background: Global nurse shortages are requiring that organizations either consider beginning to, or alternatively increase, hiring novice nurses into intensive care units (ICUs), raising important questions about preparedness for specialized practice. Understanding the experience of nursing students' ICU final placement experiences can inform education and transition supports. Objective: To explore the lived experiences of fourth-year nursing students completing their final clinical placement ("consolidation") in adult ICUs. Methods: Qualitative, interpretive phenomenological study (van Manen, 2016). Semi-structured interviews were conducted with 4 nursing students who consolidated in adult ICUs. Transcripts were thematically analysed to identify the characteristic features of the phenomenon. Results: Experiences aligned temporally following a before, during, and after timeline, summarized as "a supported learning journey." Prior exposure to critical care (coursework, clinical, personal) shaped placement preferences and readiness. Students proactively sought resources and mentorship to reduce uncertainty. Students faced steep learning curves, unpredictability, and emotional intensity. Growth was fostered by preceptors and interdisciplinary teams, hands-on participation, and developing therapeutic communication with patients and families. Consolidation was emotionally demanding yet professionally transformative, strengthening foundational skills, confidence, and interest in advanced roles. Implications for Education and Practice: Programs and units should provide structured mentorship beyond graduation, simulation-based and reflective learning to reduce anxiety, and resilience-building resources to promote psychological safety. Clear pathways for professional development in critical care and advanced practice should also be considered. Conclusions: ICU consolidation can be a transformative step from student to professional nurse, cultivating resilience, competence, and confidence when supported appropriately.
Keywords: Lived Experience; Phenomenology; Nursing; Nursing Student; ICU; Intensive Care Unit; Critical Care